Memória, Saúde e Pobreza: Narrativas do Sanitarista e Farmacêutico Rodolfo Teófilo em Finais do Século XIX Começos do Século XX, no Ceará - Garcia, Ana Karine Martins (Trabalhos de Antropologia e Etnologia, 2020)
This research refers to the migrants who were oppressed, rejected and ignored during the 1877-1879 drought in Fortaleza. Such migrants fought for their survival and resisted a city that imposed them behavioral disciplines. Sources such as: newspapers, memorialists, reports, posture codes and also the literary works “A Hunger” by Rodolfo Teófilo and “Os Retirantes” by José do Patrocínio made it possible to construct a narrative where it was possible to perceive the learning made by these various “sertanejos” who began to live and resist the weather and customs determined by the city and its inhabitants during the drought of 1878 to 1879.